Concurrent Chemoradiotherapy with Vinorelbine plus Split-Dose Cisplatin may be an Option in Inoperable Stage III Non-Small Cell Lung Cancer: A Single-Center Experience - Mertsoylu, Hüseyin (Med Sci Monit, 2015)
BACKGROUND: Concurrent chemoradiotherapy is the current standard treatment for inoperable stage III non-small cell lung cancer (NSCLC). In this study we aimed to investigate the efficacy and toxicity of CCRT with split dose of cisplatin (30 mg/m(2)) and vinorelbine (20 mg/m(2)) in patients with inoperable stage III NSCLC followed in our oncology clinic. MATERIAL/METHODS: Medical records of 97 patients with inoperable stage III NSCLC treated with concurrent chemoradiotherapy with cisplatin-vinorelbine were retrospectively analyzed. Cisplatin (30 mg/m(2)) and vinorelbine (20 mg/m(2)) were administered on days 1, 8, 22, and 29 during radiotherapy. Two cycles of consolidation chemotherapy were given. All patient data, including pathological, clinical, radiological, biochemical, and hematological data, were assessed retrospectively using our database system. RESULTS: Our study included 97 unresectable stage III NSCLC patients who were treated with CCRT. Median age was 58 years old (range 39–75) and 87 (89.7%) of the patients were men. ECOG performance score was 0–1 in 93 patients (95.9%). Squamous histology, the most common histology, was diagnosed in 46 patients (47.4%). Median follow-up time was 23.8 months. Median progression-free survival (PFS) and median overall survival time (OS) were 10.3 months and 17.8 months, respectively. Objective response rate and clinical benefit rate were 75.3% and 83.5%, respectively. Distant and local relapse rate were 57.1% and 42.9%, respectively. Hematological and non-hematological grade 3–4 toxicities were seen in 13 (13.4%) and 16 (16.5%) patients, respectively. Six (6.1%) patients died due to toxicity. CONCLUSIONS: The results of this study suggest that split-dose cisplatin may offer fewer grade III–IV toxicities without sacrificing efficacy and could be an option in patients with inoperable stage III NSCLC during CCRT. Similar to past studies, despite high response rate during CCRT, distant relapse is the major parameter that influences patient survival in long-term in NSCLC.